Exploring C*-Algebra: Central Sequences and Some Results - Kumar, Nand Kishor; Pokhrel, Chudamani (Tribhuvan University Journal, 2024)
We study central sequences of C*-algebras and find associations of the central sequences of a C*-algebra and its depictions with applications. Overall, results on central sequences are crucial for understanding the algebraic and topological properties of various mathematical structures, especially in functional analysis and operator theory. In order to understand the structure and characteristics of C*-algebras, central sequences are essential. In this paper, we investigate the notion of core sequences in C*-algebras and talk about several important conclusions associated with them. First, we give a definition of central sequences and show how crucial they are to the theory of C*-algebras. We then discuss Kadison's Central Sequence Theorem, a basic result that uses central sequences to characterize several characteristics of C*-algebras. We also go over the uses of central sequences in functional analysis, operator theory, and quantum physics, among other branches of mathematics. This article attempts to give a greater knowledge of central sequences and their function in the theory of C*-algebras through a examination and accompanying results. A key concept in C*-algebra theory are central sequences, which clarify the complex interactions between geometric features, algebraic structure, and functional analysis. Mathematicians and physicists are gaining new insights into the properties of C*-algebras through the study of central sequences and the results that go along with them. This is contributing to our understanding of these fundamental mathematical objects and the wide range of applications they have in other fields.